Comparison of the structure of (E)‐2‐(2‐benzylidenehydrazinylidene)quinoxaline with those of its chloro‐ and bromobenzylidene analogues. (12th July 2013) - Gomes, Ligia Rebelo; Low, John Nicolson; Rodrigues, Ana S. M. C.; Wardell, James L.; de Souza, Marcus V. N.; Noguiera, Thais C. M.; Pinheiro, Alessandra C.
<x xml:space="preserve">Abstract</x> (E)‐2‐(2‐Benzylidenehydrazinylidene)quinoxaline, C15H12N4, crystallized with two molecules in the asymmetric unit. The structures of six halogen derivatives of this compound were also investigated: (E)‐2‐[2‐(2‐chlorobenzylidene)hydrazinylidene]quinoxaline, C15H11ClN4; (E)‐2‐[2‐(3‐chlorobenzylidene)hydrazinylidene]quinoxaline, C15H11ClN4; (E)‐2‐[2‐(4‐chlorobenzylidene)hydrazinylidene]quinoxaline, C15H11ClN4; (E)‐2‐[2‐(2‐bromobenzylidene)hydrazinylidene]quinoxaline, C15H11BrN4; (E)‐2‐[2‐(3‐bromobenzylidene)hydrazinylidene]quinoxaline, C15H11BrN4; (E)‐2‐[2‐(4‐bromobenzylidene)hydrazinylidene]quinoxaline, C15H11BrN4. The 3‐Cl and 3‐Br compounds are isomorphous, as are the 4‐Cl and 4‐Br compounds. In all of these compounds, it was found that the supramolecular structures are governed by similar predominant patterns, viz. strong intermolecular N—H...N(pyrazine) hydrogen bonds supplemented by weak C—H...N(pyrazine) hydrogen‐bond interactions in the 2‐ and 3‐halo compounds and by C—H...Cl/Br interactions in the 4‐halo compounds. In all compounds, there are π–π stacking interactions.